On Space-Time Changes of Hedonic Prices for Single Family Houses - Krister Sandberg (European Regional Science Association (ERSA), 2002)
In this paper we estimate hedonic prices for single-family houses in two Swedish counties between the years 1994 and 2000. Structural and neighbourhood characteristics together with accessibility measures are used as attributes in the hedonic price function. Since there are indications of spatial dependence we estimate the hedonic price functions using Spatial Autoregressive Maximum Likelihood. Besides the two county capitals other local centres are found to influence the prices. The importance of the attributes also changes over both space and time.
Keywords: 330